Complications, effectiveness, and long term follow-up of fecal microbiota transfer by nasoduodenal tube for treatment of recurrent Clostridium difficile infection - van Beurden, Yvette H (United European Gastroenterol J, 2016)
BACKGROUND: Fecal microbiota transfer (FMT) is an effective treatment for recurrent Clostridium difficile infection (CDI), but data on procedure-related complications and long-term outcome are scarce. METHODS: All patients treated with FMT for recurrent CDI at the Academic Medical Center between July 2010 and January 2016 were included. FMT was performed according to the FECAL trial protocol: administration of fresh donor feces (related or unrelated donor) through a duodenal tube after pre-treatment with vancomycin and bowel lavage. We collected information on FMT-related complications, recurrent CDI, and short- and long-term adverse events by telephone interviews using a structured questionnaire at three months after FMT, and at the time of data collection of this study. RESULTS: In total, 39 patients were treated with FMT. The primary cure rate (no recurrence ≤8 weeks after one infusion with donor feces) was 82% (32 of 39 patients). Of the seven patients with recurrent CDI after FMT, four were cured by antibiotic therapy alone (fidaxomicin in three patients, metronidazole in one patient) and three by repeat FMT. Peri-procedural complications occurred in five patients, comprising fecal regurgitation or vomiting. One patient died one week post-FMT due to pneumonia; a causal relation with FMT could not be excluded. The follow-up period ranged between 3 and 68 months. No long-term side effects were reported. CONCLUSIONS: Our data underline the efficacy of FMT as treatment for recurrent CDI. Importantly, it is possible to cure post-FMT recurrences with antibiotic therapy alone. Peri-procedural complications do occur and should be closely monitored to help identify high-risk patients. To minimize the risk of complications, all FMT candidates should be evaluated to assess the most ideal delivery method.